Implementation of Blended Learning: An Alternative for Developing Technology-Based Islamic Religious Education Learning Models - Musanna, Syarifah; Walidin, Warul; Mahmud, Salami (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to analyze the implementation of blended learning as an alternative development of technology-based Islamic Religious Education (PAI) learning model. In the context of increasingly digitized education, blended learning combines face-to-face learning with online learning, allowing students to learn flexibly anywhere and anytime. From the analysis of various sources, it is concluded that blended learning is an effective method to improve the quality of technology-based Islamic Education learning. This study aims to analyze the implementation of blended learning as an alternative learning model development for technology-based Islamic Education (PAI). In the context of evolving education, blended learning is a relevant alternative learning model to increase the effectiveness and flexibility of learning. The research method used islibrary research with a qualitative approach, which involves analyzing various literature sources, including articles, journals, and related books. The results show that the application of blended learning in Islamic education learning has a positive impact on student learning outcomes. This model allows a combination of face-to-face learning and online learning, so that students can access materials more widely and interactively. The research also identified several factors supporting the success of blended learning.